α-Glucosidase inhibitor produced by an endophytic fungus, Xylariaceae sp. QGS 01 from Quercus gilva Blume - Anastasia Wheni Indrianingsih; Sanro Tachibana (Food Science and Human Wellness)
Xylariaceae sp. QGS 01, an endophytic fungus isolated from the stem of Quercus gilva Blume showed high α-glucosidase inhibitory activity. α-Glucosidase inhibitor have the role as one of carbohydrate-hydrolyzing enzymes to postpone absorption of glucose in the digestive organs. The α-glucosidase inhibitor constituents were isolated from the ethyl acetate extract of the mycellium of endophytic fungi Xylariaceae sp. QGS 01 using a bioassay-guided fractionation technique. Further separation and purification of the active fraction led to the isolation of constituents with strong inhibitory activities against α-glucosidase: 8-hydroxy-6,7-dimethoxy-3-methylisocoumarine (1) with inhibitory concentration (IC50) values against α-glucosidase from Saccharomyces cerevisiae of 41.75 μg/mL, while quercetin as the standard had an IC50 value of 4.80 μg/mL. The results of the present study showed that the endophytic fungus Xylariaceae sp. QGS 01 is potentially a rich source of antidiabetic medicine.